Acheulian hafting: Proximal modification of small flint flakes at Gesher Benot Ya'aqov, Israel. (8th August 2016) - Alperson-Afil, Nira; Goren-Inbar, Naama
Abstract: Analyses of the flint assemblages of Gesher Benot Ya'aqov have provided new insights into the technological and typological characteristics of its Acheulian Technocomplex. As these assemblages are products of small flint nodules, the flakes and flake tools are small in size. Analysis of the striking platforms of these flakes showed that modifications of different types occurred at their proximal end, resulting in the removal of the striking platform and its periphery. This phenomenon is so common that we were able to identify five distinct morphotypes of proximal modifications. We suggest that the precise and difficult task of removing a topographical high relief from the ventral face of a small flake was a specific planned goal that was aimed at acquiring a desired surface, in this case even and flat. The precision and repetition required for this, as well as the morphological diversity of the proximal ends, imply that these modifications should be interpreted as preparation for hafting.